Current Positron Studies on the Modifications of the Molecular Packing in Green-Based Polymers Through Changes in the Synthesis Procedures or Environmental Conditions - Consolati, Giovanni (2024)
The sensitivity of positron annihilation characteristics to changes in the molecular packing in network-forming polymers has been demonstrated since the early 1980s. Positron annihilation lifetime spectroscopy (PALS) is a unique technique that can provide direct information on the free volume in polymers through the experimental parameters of the free volume hole distribution, their mean value, and volume fraction. This knowledge is currently applied for PALS investigations on the main processes that govern the molecular organization in some green polymers when subjected to different synthesis procedures or environmental conditions (humidity, physical aging, temperature). In this article, which includes a wide repertoire of works published in the last two decades, results of PALS studies on eco-sustainable polymer systems based on starch, chitosan, or vegetable oils, are analyzed and discussed. Many examples are taken from the direct experience of the authors.